The Effect of Entrepreneurial Behavior and Organizational Innovation on MSMEs Performance - Lisa, Oyong (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2019)
Performance is a reflection of the organization's ability to manage and allocate its resources. This study aims to analyze the influence of entrepreneurial behavior and organizational innovation simultaneously and partially on the performance of MSMEs organization in Lumajang Regency, as well as to analyze the dominant variable affecting organizational performance. The sample in this research is 40 SMEs with questionnaire as the data collection method. The analysis technique used in this research is multiple regression analysis. The result of the analysis shows that entrepreneurship behavior and organizational innovation influence simultaneously and partially influence organizational performance. Organizational innovation has a dominant influence on organizational performance.Â